2022
DOI: 10.3889/oamjms.2022.8703
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of HHV-8 Infection among HIV-positive Individuals Residing in Bali, Indonesia

Abstract: Background: Human herpesvirus 8 (HHV-8) is considered as the etiological agent of Kaposi’s sarcoma (KS). In people living with human immunodeficiency virus (HIV) (PLHIV), KS defines acquired immunodeficiency syndrome (AIDS). Previous study found that HIV-positive individuals were more likely to be HHV-8 seropositive than HIV-negative individuals. Reports regarding the presence of HHV-8 and HIV co-infection in Indonesia is severely limited.   Aim: This study aimed to identify HHV-8 infection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…4 The Ministry of Health of Indonesia in 2020 reported that only 14% were known to be virally suppressed after 6 months of ART. 5 HIV-2 is endemic in several West African countries, namely Guinea-Bissau, Senegal, Cape Verde, Gambia, Mali, Sierra Leone, Cote d'Ivoire, and Nigeria, with a prevalence rate of 1%. Beyond West Africa, cases have also surfaced in South America, Europe, Asia, and the United States.…”
Section: Introductionmentioning
confidence: 99%
“…4 The Ministry of Health of Indonesia in 2020 reported that only 14% were known to be virally suppressed after 6 months of ART. 5 HIV-2 is endemic in several West African countries, namely Guinea-Bissau, Senegal, Cape Verde, Gambia, Mali, Sierra Leone, Cote d'Ivoire, and Nigeria, with a prevalence rate of 1%. Beyond West Africa, cases have also surfaced in South America, Europe, Asia, and the United States.…”
Section: Introductionmentioning
confidence: 99%